Research on the Effect of the Addition of Trembesi Leaf Extract on Motorcycle Exhaust Emissions - Bayu Dwi Laksana; Ali Akbar (Procedia of Engineering and Life Science, 2022)
One of the reasons for the air pollution that occurs at this time is the emission of the motorcycle exhaust. According to some sources, the trembesi leaves can absorb the level of exhaust emissions. By making extracts from trembesi leaves and added to the exhaust part of the motorcycle. Because the exhaust part is the last place of discharge of combustion waste from the combustion process that occurs on motorcycles and the result is that when the motorcycle has not been added trembesi leaf extract can produce a level of emission of Nitrogen Oxide (Nox) exhaust gases of 0.21 ppm. While the results are different when already added trembesi leaf extract can produce a level of emission of Nitrogen Oxide (NOx) exhaust gases of 0.16 ppm So it can be concluded that trembesi leaf extract can absorb or reduce the level of emission of Nitrogen Oxides (NOx), and meet the requirements of nitrogen oxide (NOx) exhaust emission levels applied in Indonesia, which is 0.17 for speeds below 1300 rpm.